JURISDICTIONAL AND CHOICE OF LAW ISSUES FOR E-COMMERCE IN MALAYSIA - Safri, Robiaaton Adawiyah; Mohamad, Ani Munirah (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
In Malaysia, there has been a significant emergence of e-commerce in recent years. Malaysia is one of the countries that is promoting the e-commerce industry in full. However, the consumers had also been wary and cautioned on the legal issues that may be arising from e-commerce transactions. The fear of being defrauded and jumping into a state of litigation on the subject matter arising from the online transaction are among the perceived risks that are contemplated by the consumers. Therefore, this research investigated what are the jurisdictional and choice of law issues involving e-commerce disputes in Malaysia? The socio-legal approach has been used which involves the collection of primary and secondary data. The study found the jurisdictional and choice of law issues that arose from e-commerce transactions. In addition, the study also found out that the current legal framework that governs e-commerce transactions in Malaysia does not specifically govern for the jurisdictional and choice of law issues. This will create a perceived risk for consumers engaging in e-commerce transactions in which the consumers involved in e-commerce should receive the same legal protection as those in traditional markets. Although there have been few strategies and steps taken by the government to provide awareness and warn to the consumers in transacting online, it does not cover them in full. Thus, this study is significant as it revealed the legal issues specifically in jurisdictional and choice of law issues that should also be looked into to avoid any dispute in e-commerce transactions. The legal framework on these issues also needs to be looked into as there are still many loop holes to be filled and few amendments are suggested to improve on it.